2020
DOI: 10.1213/ane.0000000000004682
|View full text |Cite
|
Sign up to set email alerts
|

Regional Anesthesia in Cardiac Surgery: An Overview of Fascial Plane Chest Wall Blocks

Abstract: Optimal analgesia is an integral part of enhanced recovery after surgery (ERAS) programs designed to improve patients’ perioperative experience and outcomes. Regional anesthetic techniques in a form of various fascial plane chest wall blocks are an important adjunct to the optimal postoperative analgesia in cardiac surgery. The most common application of fascial plane chest wall blocks has been for minimally invasive cardiac surgical procedures. An abundance of case reports has been described in the anesthesia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(103 citation statements)
references
References 68 publications
1
100
0
2
Order By: Relevance
“…The PECS I block targets the medial and lateral pectoral nerves and may block the intercostobrachial nerve and the intercostal nerve (ICN) branches anteriorly (31). The PECS II block targets the long thoracic nerve and thoracodorsal nerve (31).…”
Section: Pectoralis Fascial (Pecs) I and Ii Blocksmentioning
confidence: 99%
See 1 more Smart Citation
“…The PECS I block targets the medial and lateral pectoral nerves and may block the intercostobrachial nerve and the intercostal nerve (ICN) branches anteriorly (31). The PECS II block targets the long thoracic nerve and thoracodorsal nerve (31).…”
Section: Pectoralis Fascial (Pecs) I and Ii Blocksmentioning
confidence: 99%
“…The PECS I block targets the medial and lateral pectoral nerves and may block the intercostobrachial nerve and the intercostal nerve (ICN) branches anteriorly (31). The PECS II block targets the long thoracic nerve and thoracodorsal nerve (31). The literature evaluating PECS blocks for MICS is sparse, there are several reports of it being used with varying success in TA TAVI procedures (32).…”
Section: Pectoralis Fascial (Pecs) I and Ii Blocksmentioning
confidence: 99%
“…It is not known which block is superior in cardiac surgery via either approach, but there are theoretical advantages to an ESP block for sternotomy. 10,[13][14][15] Another group from the authors' hospital reported 3 pediatric patients (age 3 days, 14 days, and 4 years) who received an SAP block before coarctation repair via thoracotomy. They received less postoperative opioid and had a shorter LOS compared with historic controls.…”
Section: Discussionmentioning
confidence: 99%
“…Interfascial plane blocks play an emerging role in perioperative pain management. 83 Due to the risks associated with epidural and paravertebral techniques, interfascial plane blocks (see Table 10) are a safer alternative for patients after cardiac surgery and can be incorporated readily into a multimodal pain management plan for a number of cardiac, thoracic, and vascular procedures, due to their relative ease of performance and low level of complications. 84,85 The implementation of these blocks into multimodal cardiac enhanced recovery pathways helps to minimize opioid consumption, reduce nausea and vomiting, reduce postoperative ventilatory time, improve patient satisfaction, and provide cost reductions.…”
Section: Vascular Ultrasound (Vus)mentioning
confidence: 99%